PEMANFAATAN AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN PENGENALAN NAMA BUAH DAN SAYUR UNTUK ANAK USIA DINI BERBASIS ANDROID - Muhamad Ardy Kurniawan; Munawaroh (Journal of Research and Publication Innovation, 2024)
Augmented Reality is a technology that combines two-dimensional or three-dimensional virtual objects into a real environment and then views these virtual objects in real time. The development method applied in depicting user activities uses the Multimedia Development Life Cycle (MDLC) method with depiction of activities and the application of Unified Manipulation Language (UML) and diagrams such as: Use Case, Activity, Sequence. In the world of education, Augmented Reality provides an innovative learning space by combining digital learning materials with real space. Augmented Reality has a positive impact with its potential to project objects, such as text, images, videos, and 3D objects in the real world, so that it can provide an overview of everything that is conceptual or abstract. With the application of learning media for introducing fruits and vegetables designed using the Unity 3D application as a software maker application, Making marker cards using Adobe Photoshop can attract early childhood in learning the names of fruits and vegetables. The appearance of the learning media application for recognizing fruit and vegetable names is designed using Blender, for 3D creation of fruits and vegetables, and Vuforia as a Software Development Kit to help create augmented reality of fruits and vegetables so that the application can provide a real picture of fruits and vegetables. User Acceptance Testing (UAT) using a questionnaire with a five-point Likert scale shows that the application for recognizing fruits and vegetables using Android-based augmented reality is very good.